Silver nanoparticles modified two-dimensional transition metal carbides as nanocarriers to fabricate acetycholinesterase-based electrochemical biosensor - Jiang, Yanjun; Zhang, Xiaoning; Pei, Lijuan; Yue, Shu; Ma, Li; Zhou, Liya; Huang, Zhihong; He, Ying; Gao, Jing (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
[Display omitted] •AChE biosensor based on Ag@Ti3C2Tx nanocomposites was fabricated by drop casting method.•Ag nanoparticles were introduced to amplify the electrochemical signal.•The AChE biosensor showed good reproducibility and anti-interference ability.•The AChE biosensor displayed a detection limit of 3.27 × 10−15 M towards malathion.•Extended application of MXene-based nanoparticle to enzymatic biosensors. The Ag@Ti3C2Tx nanocomposites were successfully synthesized via a reduction process by using the transition metal carbides (MXenes) as reducing agent and support. The obtained Ag@Ti3C2Tx nanocomposites can be deemed as a promising material in electrochemical fields. Using the Ag@Ti3C2Tx nanocomposites as nanocarriers, an acetylcholinesterase (AChE) biosensor was fabricated through drop-casting method for electrochemical detection of organophosphate pesticides (OPs), via enzymatic inhibition pathway. The proposed biosensor that combined the unique electrocatalytic properties and synergistic effects between Ti3C2Tx nanosheets and Ag nanoparticles not only facilitated the electron transfer, but also enlarged the available surface area for OPs detection. The electrochemical behaviors of the fabricated AChE biosensor were performed on an electrochemical workstation. Under optimum conditions, the AChE biosensor showed favorable affinity to acetylthiocholine chloride (ATCl) and the corresponding apparent Michaelis-Menten constant (Kmapp) value was 257.67 μM. The AChE biosensor detected malathion in the linear range from 10−14 to 10−8 M. In addition, the developed AChE biosensor exhibited satisfactory selectivity, acceptable reproducibility and good stability, which could be used for determination of malathion in a real sample (tap water) with satisfactory recoveries.